The Indian Forest Rights Act (2006): A Gender Perspective. Issue 1 (June 2017) - Sharma, Anjoo B.
It is the instinct for survival that energizes women in the remote mountain terrain into direct action, challenging the collusion between the state and timber grabbers. The unsung- and marginalized women forest dwellers have struggled in the non-violent footsteps of Gandhi, while the state has rested its oars and remained in deep slumber. The best it has offered, so far, is what is commonly called the Forest Rights Act (FRA) of 2006. The strength of the marginalized is in collective action. A space has been created to conserve forest lands in this FRA that supports conservation efforts by communities. Women forest dwellers must occupy this space collectively, more so the most marginalized amongst them. To empower women, rights incorporated under the Act need to be exercised. Adequate support to women-oriented farm/forestry-based skill development and guidance in their local settings can further add to collective action. Sustained use of forest and its minor produce shall lead to conservation, and if women as a group assert community claims and community rights, their consent will have to be sought at the time of allotting that land for other industry. If for no other reason, the community as a group shall enjoy greater bargaining power at the time of securing adequate compensation for displacement.